2008
DOI: 10.1103/physrevb.78.104106
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and optical properties ofBiFeO3andBi2FeMnO6

Abstract: BiFeO 3 and Bi 2 FeMnO 6 films were epitaxially grown on SrTiO 3 ͑001͒ substrates by pulsed-laser deposition, and their structural, magnetic, magneto-optical and optical properties were measured. In Bi 2 FeMnO 6 , Fe is mainly present in the 3+ valence state, while Mn shows multivalence states. Bi 2 FeMnO 6 exhibits low magnetization at room temperature and at 5 K indicating there is no significant B-site ordering. The BiFeO 3 film shows high optical transparency, while Bi 2 FeMnO 6 shows high absorption loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
103
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(118 citation statements)
references
References 48 publications
13
103
2
Order By: Relevance
“…Previous x-ray photoemission spectra and core-level DFT calculations have established both ions predominantly exist in the 3+ state in BiMn 0.5 Fe 0.5 O 3 [44]. DFT calculations in the R3 group for BiFeO 3 found that the local microscopic DM vectors are staggered in such a way that the net DM vector points along one of the (111) directions and has a magnitude that is specified by only two parameters α and β.…”
Section: A Atomistic Model Setupmentioning
confidence: 99%
“…Previous x-ray photoemission spectra and core-level DFT calculations have established both ions predominantly exist in the 3+ state in BiMn 0.5 Fe 0.5 O 3 [44]. DFT calculations in the R3 group for BiFeO 3 found that the local microscopic DM vectors are staggered in such a way that the net DM vector points along one of the (111) directions and has a magnitude that is specified by only two parameters α and β.…”
Section: A Atomistic Model Setupmentioning
confidence: 99%
“…[ 46 ] First of all, according to these rules, most of the possible interactions are AFM (Fe 4+ -O-Mn 3+ , Fe 3+ -O-Mn 2+ , Fe 3+ -O-Fe 3+ , Mn 2+ -O-Mn 2+ , Fe 4+ -O-Mn 2+ ). [ 14,46 ] Also the Fe 4+ -O-Fe 3+ interaction can be expected to be AFM as found in La 1− x Sr x FeO 3 . [ 47,48 ] The presence of these AFM interactions may only decrease the total M S of the superlattices.…”
Section: Doi: 101002/admi201500597mentioning
confidence: 99%
“…[ 14,19,33 ] The lower M S value of our superlattices is likely to be caused by complex effects resulting from a mixture of AFM and FM ordering which can arise from internal charge transfer leading to mixed ionic valences for Mn and Fe. [ 19 ] Also note that the in-plane BMO/BFO interface is present along the step edges.…”
Section: Doi: 101002/admi201500597mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiferroic manganite Bi2FeMnO6 (BFMO), a compound of BiFeO3 and BiMnO3, has been recently designed theoretically and fabricated experimentally. More intense research has resulted in promising findings such as multiferroic, coexisting a small net ferromagnetic magnetization at room temperature and ferroelectricity at low-temperature in BFMO [5][6][7]. In the previous work, based on the small magnetic moment observed in M-H loop, Mn-O-Mn is antiferromagnetically ordered in BFMO, which is much weaker than Fe-O-Fe ordering [8].…”
mentioning
confidence: 99%